An Analysis of nurses lived experience with digital health technologies in practice - Mohsam, Faeda (Journal of Health Informatics in Africa, 2024)
Background and Purpose: In the healthcare field, technological innovations have been introduced which are referred to as digital health technologies (DHTs). As digital technologies continue to impact the nursing profession on a global scale, nurses are increasingly required to use a variety of digital health technologies when providing direct care across the healthcare sphere. Whilst the benefits of DHTs have been empirically proven, usability problems, often encountered with usage, can be frustrating to both healthcare professionals and patients compared to other industries. The aim of this qualitative study was to understand, analyse and assess nurses’ lived experiences of using DHTs as part of their work practices. Methods: The study employed an interpretive stance and a qualitative phenomenological approach to explore the lived experiences of experienced nurses presently using DHTs in practice. In-depth interviews and observation were used to collect data from nurses in two public hospitals in Cape Town. A thematic analysis was used to organise and analyse the data acquired from the participants. The Normalization Process Theory (NPT) served as a theoretical lens to interpret the findings of this study. Purposive sampling was used to identify participants. Results: Nurses, as end-users, have found DHTs to be relevant to their work practices and compatible with their existing work practices. It was found that, through the use of technology, nurses’ tasks have become easier and more time‑efficient, and as a result, nursing quality is improved. Conclusions: Findings indicate that DHTs have been fully embedded into their daily work activities as patient care is optimised. Nurses positively appreciate technologies, to the extent that they cannot do their work without DHTs, and this is substantiated by their desire to learn new technology, not only to optimise patient care but to augment their knowledge and skill. Keywords: nurse, digital health, digital health technology, lived experience, normalisation process theory.